Investigating the zero lower bound on the nominal interest rate under financial instability - Julio A. Carrillo; Céline Poilly (Banco de México, 2014)
This paper studies the effects of three financial shocks in the economy: a net-worth shock, an uncertainty or risk shock, and a credit-spread shock. We argue that only the latter can push the nominal interest rate against its zero lower bound. Further, a recessionary shock to the net worth or the credit spread generates a positive response for loans, which is counter-intuitive during an economic downturn. Finally, we find that there is an optimal commitment period for the central bank to keep the nominal interest rate equal to zero (forward guidance) after a financial turmoil. Beyond that optimal period, the volatility of inflation and output rise quick and sharply. Thus, an excessive forward guidance policy may destabilize the economy.
Keywords: E31; E44; E52; E58; 330; Zero Lower Bound; Financial Accelerator; Financial Shocks